Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 9 - Mid-Chapter Check Point - Page 716: 32



Work Step by Step

RECALL: (1) $\log_b{m} - \log_b{n} = \log_b{(\frac{m}{n})}$ (2) $\log_b{m} + \log_b{n} = \log_b{(mn)}$ (3) $n \cdot \log_b{m} = \log_b{(m^n)}$ Use rule (3) above to obtain: $=\log_7{(x^8)} - \log_7{(y^{\frac{1}{3}})}$ Use rule (1) above to obtain: $=\log_7{\left(\frac{x^8}{y^{\frac{1}{3}}}\right)}$ Use the rule $a^{\frac{1}{3}} = \sqrt[3]{a}$ to obtain: $=\log_7{\left(\frac{x^8}{\sqrt[3]{y}}\right)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.